(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3ef aUd GdHGA (B( (3HGH GdCda(B) (3, bhdg (B: (3HGHGA (B: (3HCHCJ GdUHiEPG bdJ HCHi CfJ hCei GdHDHD GdCUd hjbGd GdYGde hjbGd adGf ai HDHD GdcQe GHJOCJ Hg hHOCJ GdTF aYdJg EHJOGA s
(3BNQgG (B:s
(3geP(B: (3GdgeGPi GdHYjQ GdSQjY hcPdc GdfGbI ghP (B: (3ghPI GdbWGI hHgG Sei GdQLd ghPI , bGd GdCYTi (B:- (3ef jdb ghPI jSLO ZjQ eJFH EPG JYee ahb GdJGL Gh hVYG Je GdcJGH (B: s
(3HgG fXGe GdJYbjHIs
(3eged GdfbW CMjGfkGs
(3fSNI JGSYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs